(untitled) - McBride, Eve (Québec, Canada, 1995)
A collection of columns in The Montreal Gazette and The Toronto Star by popular, personal journalist Eve McBride.PUB-COMMENT: This extraordinary book was a finalist for the Stephen Leacock Award in 1996,and is now in its second printing. Eve McBride is a sought-after speaker in schools and in adult gatherings, as well as a popular journalist for The Gazette.
Keywords: Canadian fiction,Canadian literature; 20th century